PENGARUH KESADARAN MEREK, PERSEPSI KUALITAS, LOYALITAS MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ULANG KONSUMEN SEPATU MEREK ASICS (Studi pada Mahasiswa Universitas Brawijaya Malang) - Wardhana, Bagaskara Girindra (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the effect of brand awareness, perceived quality, brand loyalty and price on Asics brand shoes re-purchase decisions. This type of research is explanatory research which explains the causal relationship between variables by testing hypothesis.The study population were students at the University of Brawijaya Malang that have Asics brand shoes. The samples using purposive sampling with a sample size of 100 students. To determine the influence of the brand awareness, perceived quality, brand loyalty and price on Asics brand shoes re-purchase decisions use multiple regression analysis. Hypothesis test results stating that the variable of brand awareness, perceived quality, brand loyalty and price have an appropriate model to measure the re-purchasing decision. But partially, variable brand awareness and perception of quality has no significant effect, brand loyalty and price significantly influence re-purchasing decisions. This shows that the re-purchasing decisions Asics shoes brand will increased when variables brand awareness, perceived quality, brand loyalty and prices increased. But, brand awareness and perceived quality has no significant effect on re-purchasing decisions Asics brand shoes. From the four variables, Brand Loyalty has influence dominant variables.Keywords: Brand Awareness, Perceived Quality, Brand Loyalty, Price, Re-purchase Decision.